2008
DOI: 10.35196/rfm.2008.4.323
|View full text |Cite
|
Sign up to set email alerts
|

Variación Fenotípica Entre Y Dentro De Poblaciones Silvestres De Chile Del Noroeste De México

Abstract: Se estimó la distribución jerárquica de la variación fenotípica entre poblaciones, entre y dentro de familias, y la proporción de esta variación que tiene una base genética en cuatro poblaciones de chile silvestre (Capsicum annuum var. glabriusculum) del noroeste de México. Los caracteres medidos fueron: altura de planta, diámetro de tallo, largo de hoja, ancho de hoja, número de frutos por planta, número de semillas por fruto, número de semillas por planta y peso de semilla. De la variación total, 61.8 % se d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
(9 reference statements)
1
1
0
Order By: Relevance
“…Because plants grew in a uniform environment, these results indicate that the variation observed among and within species, morphotypes, and populations can be considered a genetic variation among and within them. These results agree with those obtained with molecular markers of isoenzymes [14], RAPDs [16], microsatellites [17], and in quantitative characteristics [24,27,28], which have indicated that the wild and domesticated Capsicum species maintain a higher genetic variation within and among populations. According to the results of this study, the strategy to identify the genetic diversity in these species consists in emphasizing the collection of a significant number of individual plants from each population.…”
Section: Distribution Of Variationsupporting
confidence: 90%
See 1 more Smart Citation
“…Because plants grew in a uniform environment, these results indicate that the variation observed among and within species, morphotypes, and populations can be considered a genetic variation among and within them. These results agree with those obtained with molecular markers of isoenzymes [14], RAPDs [16], microsatellites [17], and in quantitative characteristics [24,27,28], which have indicated that the wild and domesticated Capsicum species maintain a higher genetic variation within and among populations. According to the results of this study, the strategy to identify the genetic diversity in these species consists in emphasizing the collection of a significant number of individual plants from each population.…”
Section: Distribution Of Variationsupporting
confidence: 90%
“…In this sense, it has been interpreted that a CV above 20% as the presence of a wide variation within populations and species of the Cola [21], Pelargonium [22], Helianthus [23] genera. In Capsicum, has been reported a CV higher than 20% in six of nine quantitative characteristics measured in 19 wild populations of pepper in the Northwest of Mexico [24]. Another study in Capsicum [25] reported that of 18 measured characteristics, 13 presented a CV higher than 20% in 148 domesticated populations of C. annuum, C. frutescens, and C. chinense.…”
Section: Phenotypic Variationmentioning
confidence: 98%
“…glabriusculum phenotypic variation within families can be attributed mainly to environmental effects. Variation among families (within populations) has a genetic basis as a part of total variation among populations (Venable & Búrquez 1989, Hernández-Verdugo et al 2008. To assess phenotypic and genetic variation, we performed a nested analysis of variance to determine the distribution of the relative quantities of phenotypic variation among regions, populations within regions, families within populations, variation within families was estimated as the residual of the ANOVA.…”
Section: Methodsmentioning
confidence: 99%
“…In wild plant species as Capsicum annuum var. glabriusculum, components of phenotypic variation within and among populations, as well as its genetic variation, are key elements that allow a species to confront changing environmental adversities and expand geographically (Rice & Mack 1991, Hernández-Verdugo et al 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation